Marketing Strategy of HITS UNIKOM Radio to Improve Brand Awareness in The Digital ERA - Katresna, N A; Wahab, D A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to describe the marketing strategy of Hits Unikom Radio in increasing Brand Awareness in this digitalization era. The method used in this research is to use a qualitative approach which is described descriptively to determine the marketing strategy in increasing Brand Awareness of Hits Unikom Radio in the digital era. The results of this study indicate that Hits Unikom Radio's marketing strategy in increasing Brand Awareness by utilizing Instagram social media is successful because there is a significant increase in the number of new followers. And this Instagram social media is a strategic target for radio with a youth segmentation. To overcome competition with other radios today, especially in Bandung, Hits Unikom Radio is very consistent with playing the latest songs that are up to date. In addition, Hits Unikom Radio also utilizes the use of other social media, such as YouTube, Facebook and Tik-Tok. However, this research will emphasize Instagram social media because in this digital era, especially radio, Instagram is a strong social media to provide information about activities that can later increase brand awareness of the listeners. So it can be concluded from this research that Hits Unikom Radio provides interesting upload content and succeeds in increasing Brand Awareness. It is proven that special events on the radio such as interviews with artists and other exciting activities can be enjoyed by old followers and even new followers. And because it has other social media so that the activity can also be watched on the youtube channel. Hits Unikom Radio can be said to be an all in one radio because it broadcasts on air, off air, and live streaming.